Property in Social Continuity - von Benda-Beckmann, F. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1979)
This book deals with the property and inheritance system of the matrilineal Minangkabau of West Sumatra in the context of legal pluralism.